Mutation of Npr2 Leads to Blurred Tonotopic Organization of Central Auditory Circuits in Mice - Lu, Cindy C.; Cao, Xiao-Jie; Wright, Samantha; Ma, Le; Oertel, Donata; Goodrich, Lisa V. (PLoS genetics, 2014)
Tonotopy is a fundamental organizational feature of the auditory system. Sounds are encoded by the spatial and temporal patterns of electrical activity in spiral ganglion neurons (SGNs) and are transmitted via tonotopically ordered processes from the cochlea through the eighth nerve to the cochlear nuclei. Upon reaching the brainstem, SGN axons bifurcate in a stereotyped pattern, innervating target neurons in the anteroventral cochlear nucleus (aVCN) with one branch and in the posteroventral and dorsal cochlear nuclei (pVCN and DCN) with the other. Each branch is tonotopically organized, thereby distributing acoustic information systematically along multiple parallel pathways for processing in the brainstem. In mice with a mutation in the receptor guanylyl cyclase Npr2, this spatial organization is disrupted. Peripheral SGN processes appear normal, but central SGN processes fail to bifurcate and are disorganized as they exit the auditory nerve. Within the cochlear nuclei, the tonotopic organization of the SGN terminal arbors is blurred and the aVCN is underinnervated with a reduced convergence of SGN inputs onto target neurons. The tonotopy of circuitry within the cochlear nuclei is also degraded, as revealed by changes in the topographic mapping of tuberculoventral cell projections from DCN to VCN. Nonetheless, Npr2 mutant SGN axons are able to transmit acoustic information with normal sensitivity and timing, as revealed by auditory brainstem responses and electrophysiological recordings from VCN neurons. Although most features of signal transmission are normal, intermittent failures were observed in responses to trains of shocks, likely due to a failure in action potential conduction at branch points in Npr2 mutant afferent fibers. Our results show that Npr2 is necessary for the precise spatial organization typical of central auditory circuits, but that signals are still transmitted with normal timing, and that mutant mice can hear even with these deficits.